Developing Lean-Based Learning Model to Improve Work Skills of Vocational Students - Hartanto, Suryo; Arifin, Zaenal; Fordiana, Ratih (Fakultas Teknik Universitas Negeri Malang, 2021)
The low absorption of the workforce in the vocational high school graduates indicate their lack of expertise and competency. It urges to improve their work skills to meet the demand of the world of work. This research aims at developing a Lean-based learning model to enhance the work skills of vocational high school students. This study can be categorized as development research using the modified Borg and Gall method. The Lean-based learning model was tested through three stages, namely its validity, effectiveness, and practicality towards students, teachers and industrial practitioners. Based on the research findings, the developed learning model can be categorized as good in case of its validity, effectiveness, and practicality. It means the lean-based learning model is valid, effective and practical as one of the alternatives to improve the competency among vocational high school students to fulfill the industrial demand.